Islamic Microfinance Institutions : A Systematic Literature Review - Khairul Anwari (Badan Penerbitan Fakultas Pertanian Universitas Ratu Samban, 2025)
Islamic microfinance plays a crucial role in fostering community empowerment and enhancing the well-being of individuals. This research contributes valuable insights through a literature review of Islamic microfinance institutions, encompassing 82 articles (available for open access) sourced from Scopus-indexed journals spanning from 2010 to 2025. In this systematic literature review, the authors also highlight research trends, identify the most influential journals, acknowledge the most prolific researchers, and delineate the countries with the highest productivity, along with other relevant factors concerning this study. The results of this research provide vital insights information for future researchers involved in studies with regard the Islamic Microfinance